Compression‐Induced Anomalous Subsidence in the Extensional Sedimentary Basin: A Numerical Study From the Pearl River Mouth Basin, Northern South China Sea Margin. Issue 18 (17th September 2021) - Li, Fucheng; Sun, Zhen; Ding, Weiwei; Yang, Hongfeng; Xie, Hui; Pang, Xiong; Li, Hongbo; Zheng, Jinyun
Abstract: Compressional uplift has long been considered as the basic response to basin inversion. However, significant discrepancies are recently observed in the Pearl River Mouth Basin (PRMB), where anomalous subsidence occurs during the Miocene compression phase. Whether the subsidence is another scenario that is associated with the tectonic inversion under certain circumstances remains unknown. Here we conduct systematic numerical modeling to explore the patterns of rift basin evolution from extension to compression. Our results show that two distinct inversion types develop depending on the stretching degree and tectonic quiescence. A less stretched continental crust would facilitate the uplift of basin center accompanied by erosion during shortening; otherwise, the basin center exhibits anomalous subsidence with abundant sediment accumulation. We further demonstrate that these two contrasting types, consistent with the Miocene evolutionary pathways of the eastern and western PRMB, respectively, are strongly conditioned by the along‐strike variation of stretching degree during extension. Plain Language Summary: Uplift was previously considered as the only evolutionary pathway during basin inversion. Our expanded modeling study has demonstrated that the response is not unique. For example, the numerical results show that, when the continental crust is highly extended (e.g., to a thickness lower than 7 km) at the end of extension, the subsequent compression would promote the development of anomalous subsidence. By contrast, uplift and erosion of the basin center will occur only when the continental crust is slightly stretched. These results compare well with the along‐strike variations observed in the Pearl River Mouth Basin (PRMB), northern South China Sea margin. The continental crust in the western PRMB has been stretched by a larger amount and thus is characterized by anomalously fast subsidence, whereas the eastern PRMB has undergone a smaller amount of crustal stretching and then is uplifted by several kilometers during the basin inversion. Key Points: The central uplift accompanied by erosion or subsidence with abundant sediment accumulation may develop during the basin inversion Crustal thickness and tectonic quiescence are crucial factors determining whether the basin center will be uplifted or subsided Variation in the crustal thickness may be a mechanism for the different evolutionary pathways along the strike of the Pearl River Mouth Basin